Putting down roots: afforestation and bank cohesion of Icelandic rivers - Rathburn, Sara; Eysteinsson, Þröstur; Sæmundsson, Þorsteinn; Kemper, John T.; Wieting, Celeste; Friedman, Jonathan M. (Zenodo, 2023)
Riparian vegetation is widely recognized as a critical component of functioning fluvial systems. Human pressures on woody vegetation including riparian areas, especially at high latitude, have had lasting effects. In Iceland, prior to human settlement, native downy birch woodlands covered approximately 15–40% of the land area compared to 1–2% today. Afforestation efforts include planting seedlings, protecting native forest remnants, and acquiring land areas as national forests. The planted and protected nature of vegetation along rivers within some forests provides a unique opportunity to evaluate the various taxa within riparian zones and the channel stabilizing characteristics of the vegetation used in afforestation. We investigated bank properties, sediment textures, and root characteristics within riparian zones along four rivers in forests in Iceland. Bank sediment textures are dominantly sandy loam overlying coarser textures. Undercut banks are common because of erosion of the less cohesive subsurface layer. Quantitative root data indicate that the woody taxa have greater root densities, rooting depths, and more complex root structures than forbs or graminoids. The native downy birch has the highest root densities, with <1 mm roots most abundant. Modeling of added bank cohesion indicates that willow provides up to 6 times and birch up to 4 times more added cohesion to the coarse sediment textures comprising stream banks compared to no vegetation. We conclude that planting and protecting the native birch and willow helps to reduce bank erosion, especially where long-term grazing exclusion can be maintained. Microsoft Excel. Funding provided by: Fulbright Association Crossref Funder Registry ID: http://dx.doi.org/10.13039/100010629 Award Number: Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: